Design and ergonomic assessment of a passive head/neck supporting exoskeleton for overhead work use. (May 2022) - Garosi, Ehsan; Mazloumi, Adel; Jafari, Amir Homayoun; Keihani, Ahmadreza; Shamsipour, Mansour; Kordi, Ramin; Kazemi, Zeinab
Abstract: Overhead work is an important risk factor associated with musculoskeletal disorders of the neck and shoulder region. This study aimed to propose and evaluate a passive head/neck supporting exoskeleton (HNSE) as a potential ergonomic intervention for overhead work applications. Fourteen male participants were asked to perform a simulated overhead task of fastening/unfastening nut in 4 randomized sessions, characterized by two variables: neck extension angle (40% and 80% of neck maximum range of motion) and exoskeleton condition (wearing and not wearing the HNSE). Using the HNSE, significantly alleviated perceived discomfort in the neck (p-value = 0.009), right shoulder (p-value = 0.05) and left shoulder (p-value = 0.02) and reduced electromyographic activity of the right (p-value = 0.005) and left (p-value = 0.01) sternocleidomastoid muscles. However, utilizing the exoskeleton caused a remarkable increase in right (p-value = 0.04) and left (p-value = 0.05) trapezius electromyographic activities. Performance was not significantly affected by the HNSE. Although the HNSE had promising effects with respect to discomfort and muscular activity in the static overhead task, future work is still needed to investigate its effect on performance and to provide support for the generalizability of study results. Highlights: A new head/neck supporting exoskeleton (HNSE) was designed and evaluated for overhead work applications. Using the proposed HNSE significantly reduced perceived discomfort in neck and right/left shoulder. Wearing HNSE reduced sternocleidomastoid muscle activity, while the activity of trapezius was increased. Although the performance was improved by using the HNSE, the results were not significant.